What works in improving gender equality : international best practice in childcare and long term care policy - Rummery, Kirstein; McAngus, Craig; Edwards, Alcuin (Policy Press, 2021)
EPDF and EPUB available Open Access under CC-BY-NC licence. This book provides an accessible analysis of what gender equality means and how we can achieve it by adapting best practices in childcare and long term care policies from other countries.